Association between perceptions of antiretroviral drug use and medication adherence in patients with human immunodeficiency virus - Muthmainnah; Katu, Sudirman; Tabri, Nur Ahmad; Syamsuddin, Saidah; Bakri, Syakib; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The effectiveness of antiretroviral therapy (ART) is determined by both antiretroviral (ARV) drugs and patient adherence. Positive perceptions of ART among people living with HIV and AIDS (PLHIVs) are crucial for maintaining good adherence; thus, negative beliefs about ARV drugs can result in lower ART effectiveness. This study analyzed the association between perceptions of ARV drug use and other medication adherence factors in patients with HIV. Methods: This observational, cross-sectional study included 102 PLHIVs to retrospectively assess adherence to ART through self-reports of patients while they were receiving ART. Perceptions of ARV drug use were evaluated with the Beliefs about Medicines Questionnaire. Statistical analysis was performed with the chi-square test, independent t-test, and Mann-Whitney test. Statistical significance was described as a p-value of <0.05. Results: Most participants (86.3%) exhibited good adherence. Participants with good adherence had stronger beliefs and positive perceptions about the benefits of ART (p = 0.915). They also had lower perceptions about the potential adverse effects of ARV drugs than participants with moderate or low adherence (p = 0.608). A CD4 T-cell count ³ 200 cells/mm3 was significantly associated with medication adherence (p < 0.001), but no other significant associations were observed between sociodemographic/other factors (i.e., side effects of ARV drugs, duration of ART, and number of ARV tablets) and medication adherence. Conclusions: Perceptions of ARV drugs were not significantly associated with medication adherence in patients with HIV. The only significant influencing factor was a CD4 T-cell count of ³200 cells/mm3.